Packaging of Brome Mosaic Virus RNA3 Is Mediated through a Bipartite Signal - Choi, Yoon Gi (American Society for Microbiology, 2003)
The three genomic and a single subgenomic RNA of brome mosaic virus (BMV), an RNA virus infecting plants, are packaged by a single-coat protein (CP) into three morphologically indistinguishable icosahedral virions with T = 3 quasi-symmetry. Genomic RNAs 1 and 2 are packaged individually into separate particles whereas genomic RNA3 and subgenomic RNA4 (coat protein mRNA) are copackaged into a single particle. We report here that packaging of dicistronic RNA3 requires a bipartite signal. A highly conserved 3′ tRNA-like structure postulated to function as a nucleating element (NE) for CP subunits (Y. G. Choi, T. W. Dreher, and A. L. N. Rao, Proc. Natl. Acad. Sci. USA 99:655-660, 2002) and a cis-acting, position-dependent packaging element (PE) of 187 nt present in the nonstructural movement protein gene are the integral components of the packaging core. Efficient incorporation into BMV virions of nonviral RNA chimeras containing NE and the PE provides confirmatory evidence that these two elements are sufficient to direct packaging. Analysis of virion RNA profiles obtained from barley protoplasts transfected with a RNA3 variant lacking the PE provides the first genetic evidence that de novo synthesized RNA4 is incompetent for autonomous assembly whereas prior packaging of RNA3 is a prerequisite for RNA4 to copackage.